PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Susi Yuliana, 09.05.52.0008; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
The objective of this study is to exmine the influence of mayoritas shareholders, institutional ownership, foreign ownership, board of commissioners, board of directors, board of commissioners of independent, and audit committee to the corporate performance of the banking companies that listed on Indonesia Stock Exchange. The population is 30 companies of banking which listed on Indonesia Stock Exchange at periode 2008-2011. Sample was chose using purposive sampling method amount to 15 companies. Technique test of data is by using multiple linier regression. The result indicates that board of directors is significant positive influence on corporate performance. Major shareholders, institutional ownership, foreign ownership, board of commissioners, board of commissioners of independent, and audit committee isnât significant influence on corporate performance.Keywords: Mayoritas shareholders, institutional ownership, foreign ownership, board of commissioners, board of directors, board of commissioners of independent, and audit committee